Probiotic-loaded microcapsule system for human in situ folate production: Encapsulation and system validation. (December 2016) - Ramos, Philippe E.; Abrunhosa, Luís; Pinheiro, Ana; Cerqueira, Miguel A.; Motta, Carla; Castanheira, Isabel; Chandra-Hioe, Maria V.; Arcot, Jayashree; Teixeira, José A.; Vicente, António A.
Abstract: This study focused on the use of a new system, an alginate | Ɛ-poly- l -lysine | alginate | chitosan microcapsule (APACM), able to immobilize a folate-producing probiotic, Lactococcus lactis ssp. cremoris (LLC), which provides a new approach to the utilization of capsules and probiotics for in situ production of vitamins. LLC is able to produce 95.25 ± 26 μg·L − 1 of folate, during 10 h, and was encapsulated in the APACM. APACM proved its capacity to protect LLC against the harsh conditions of a simulated digestion maintaining a viable concentration of 6 log CFU·mL − 1 of LLC. A nutrients exchange capacity test, was performed using Lactobacillus plantarum UM7, a high lactic acid producer was used here to avoid false negative results. The production and release of 2 g·L − 1 of lactic acid was achieved through encapsulation of L. plantarum, after 20 h. The adhesion of APACM to epithelial cells was also quantified, yielding 38% and 33% of capsules adhered to HT-29 cells and Caco-2 cells, respectively. Graphical abstract: Highlights: Folic acid has inefficient absorption, whilst natural forms have better uptake. Coated microcapsules are able to protect probiotics against the harsh conditions of the stomach. Coated microcapsules are able to exchange nutrients allowing probiotics activation. Coated microcapsules are able to adhere to epithelial cells.